Pedicled Omentoplasty for Treatment of Rheumatoid Nodule Pneumothorax: A Case Report - Matsumiya, Hiroki; Kuroda, Koji; Hashimoto, Teppei; Tanaka, Fumihiro (The Thoracic and Cardiovascular Surgeon Reports, 2024)
Background No consensus exists regarding surgical intervention for rheumatoid nodule–related pneumothorax. Clinical policy decisions rely on individual clinicians' experience and are usually intractable.Case Description A 50-year-old man with a difficult-to-treat rheumatoid arthritis–related pneumothorax was successfully treated with pedicle omentoplasty without recurrence at approximately 2 years posttreatment. To the best of our knowledge, this is the first report of a patient where pneumothorax did not recur due to firm adhesions despite fluctuating postoperative rheumatoid nodules, as captured by regular computed tomography imaging follow-ups.Conclusion Pedicled omentoplasty is effective for rheumatoid nodule–related pneumothorax as it reduces pneumothorax recurrence.
Keywords: pedicled omentoplasty; omentum; rheumatoid pleural nodules; intractable secondary pneumothorax; rheumatologists